Onerice breeding framework: An end-to-end system to develop better varieties faster - Bhosale, Sankalp; Thathapalli Prakash, Parthiban; Kadaru, Suresh Babu; Hussain, Waseem; Dixit, Shalabh; Ali, Jauhar; Platten, John D.; Islam, Md Rafiqul; Singh, Vikas Kumar; Murori, Rosemary; Ndayiragije, Alexis; Panchbhai, Ajay; et al. (Wiley, 2025)
Breeding in the Consultative Group on International Agricultural Research (CGIAR) system is an intricate process that integrates the contributions of market research, pre-breeding, breeding, breeding operations, and seed systems. Therefore, a well-defined framework is critical for the effective and efficient operation of a breeding program. The OneRice Breeding Framework developed at the International Rice Research Institute (IRRI) integrates these components, from initial market research to establish breeding goals, creating breeding strategies for improved product design and development, and swiftly testing and replacing products through effective seed systems. The framework represents a cutting-edge breeding approach that offers comprehensive guidance on harnessing modern tools and technologies, including genomic selection, speed breeding, sparse testing, and so on. Additionally, the framework outlines strategies for systematically integrating novel genetic variation into elite breeding programs through pre-breeding efforts. It is adaptable across different crops and is dynamic, allowing adjustments in the breeding program based on target objectives, resource availability, and tools. The OneRice Breeding Framework is a comprehensive end-to-end framework that integrates all the components to enhance genetic gains and develop and disseminate better products faster to address food, nutrition, and income security. Consequently, the OneRice Breeding Framework is the fundamental blueprint for modern rice (Oryza sativa) crop breeding.